DAMPAK ALIH FUNGSI LAHAN PERTANIAN CENGKEH TERHADAP KONDISI SOSIAL EKONOMI PETANI (Studi Kasus Petani Pemilik Lahan di Kelurahan Kumelembuai Kecamatan Tomohon Timur) - River Pieter Tandaju; Elsje P. Manginsela; Nordy F. L. Waney (AGRI-SOSIOEKONOMI, 2017)
The research aims to describe the impact of the conversion of agricultural land of cloves to the socio-economic condition of farmers. The study was conducted from May to July 2017. The data used are primary data obtained through interviews to 5 (five) respondents who sell land for land converted. Secondary data is obtained from Tetetana Hill nature reserve, Kumelembuai village government, books and journals. Data analysis used is descriptive analysis. The research results showed that viewed from the economic side, land conversion has a positive impact for the farmers family and local society. Positive impacts for farmers family include increasing the income, helping to construction the house of farmers, opening up a new farming businesses, and for local society like existence of jobs. Viewed from the social side, land conversion has positive and negative impacts, that is: change of farmers family life status (positive impact), and the influence of visitor habits toward society (negative impact).